2011
DOI: 10.4049/jimmunol.1003565
|View full text |Cite
|
Sign up to set email alerts
|

Nonhematopoietic Cells Are Key Players in Innate Control of Bacterial Airway Infection

Abstract: Airborne pathogens encounter several hurdles during host invasion, including alveolar macrophages (AMs) and airway epithelial cells (AECs) and their products. Although growing evidence indicates pathogen-sensing capacities of epithelial cells, the relative contribution of hematopoietic versus nonhematopoietic cells in the induction of an inflammatory response and their possible interplay is still poorly defined in vivo in the context of infections with pathogenic microorganisms. In this study, we show that non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
56
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 50 publications
(55 reference statements)
5
56
1
1
Order By: Relevance
“…S5A and B in the supplemental material), consistent with previous studies indicating that neutrophil recruitment is T4SS dependent (20,28,30,60 identified alveolar macrophages as being positive for T4SS-mediated injection, but we also could identify injected cells that expressed high levels of Ly6G and were negative for MHC-II (Fig. 3B).…”
Section: A Reporter System Tracks Translocation Of Type IV Secretion supporting
confidence: 79%
See 3 more Smart Citations
“…S5A and B in the supplemental material), consistent with previous studies indicating that neutrophil recruitment is T4SS dependent (20,28,30,60 identified alveolar macrophages as being positive for T4SS-mediated injection, but we also could identify injected cells that expressed high levels of Ly6G and were negative for MHC-II (Fig. 3B).…”
Section: A Reporter System Tracks Translocation Of Type IV Secretion supporting
confidence: 79%
“…In vivo, alveolar macrophages and neutrophils in the airway space and lung tissue were the primary recipients of T4SS-translocated effectors and harbored viable bacteria. Consistent with the critical role of immune sensing of T4SS activity in triggering host cytokine production, alveolar macrophages and neutrophils from mice infected with T4SS-competent L. pneumophila, but not T4SS-deficient bacteria, secreted the cytokines TNF and IL-1␣, which are known to be important for immune-mediated clearance of infection (28)(29)(30). We did not observe T4SS-mediated injection into other lung cell populations, including airway epithelial cells and dendritic cells, suggesting that these cells are not a primary intracellular niche for L. pneumophila and do not directly participate in cytosolic immunosurveillance of T4SS activity during lung infection.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…pneumophila infection induces a strong innate immune response, which is pivotal for the initial control of a primary L. pneumophila infection (22)(23)(24)(25). Furthermore, L. pneumophila infection also elicits an adaptive immune response that was shown to protect guinea pigs from lethal secondary L. pneumophila challenge (26,27).…”
mentioning
confidence: 99%